The cloud-based demand-driven supply chain - Sharma, Vinit, 1974- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2019)
Your road map to bringing any supply chain up to state-of-the-art performance, this practical guidebook quickly puts you in a position to make and influence highly informed decisions on customizing cloud-based strategies to optimize supply-chain performance. --
Demand-Driven Forecasting in the Supply Chain -- Introduction to Cloud Computing -- Migrating to the Cloud -- Amazon Web Services and Microsoft Azure -- Case Studies of Demand-Driven Forecasting in AWS -- Summary.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 07, 2018).
John Wiley and Sons
Keywords: Business logistics; Supply and demand -- Management; Cloud computing -- Industrial applications; Logistique (Organisation); Offre et demande -- Gestion; Infonuagique -- Applications industrielles; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business logistics; Supply and demand -- Management